PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA RESTORAN TANATAP - Muhammad Rizky Yoga; Verry Cyasmoro (Human Capital Development, 2025)
This study aims to analyze the influence of the work environment, leadership style and disturbances on all employees of Tanatap Restaurant. This study used a questionnaire with a purposive sampling method. Based on the results of research and data analysis conducted on 103 employees of Tanatap Restaurant, it can be concluded that the Work Environment has a significant partial effect on employee performance. A safe, comfortable, and supportive work environment both physically and psychologically can increase employee productivity and performance. This is proven through a t-test which shows a significance value <0.05. However, Leadership Style does not have a significant partial effect on employee performance.